Job Satisfaction of Iranian EFL Teachers: Exploring the Role of Gender, Education Level, Teaching Experience, and Service Location - Afsheen Rezai; Ehsan Namaziandost; Fidel Çakmak (Teaching English Language, 2022)
Teacher's job satisfaction (JS) is a crucial factor making objectives realized in an education system. It is deemed that various factors affect teachers' JS. This study aims to investigate if Iranian EFL teachers' JS is affected by gender, education level, teaching experience, and service location factors. For this purpose, using a stratified sampling method, a sample, including 440 female and male EFL teachers were chosen from Tehran, Lorestan, and Markazi Provinces, Iran. To collect the required data, the participants were asked to complete a printed version of a Teachers' Job Satisfaction Survey along with items addressing their demographic information (e.g., gender, education level, teaching experience, and service location). An independent sample t-test and a one-way ANOVA were used to analyze the collected data. Results evidenced no statistically significant difference between the female and male participants regarding their JS. Additionally, the findings documented that the participants with higher education levels had higher job satisfaction. Moreover, the results turned out that the participants with more teaching experiences participants felt less gratified with their jobs. Likewise, the findings disclosed that the participants working in Tehran Province enjoyed higher JS than the teachers working in Lorestan and Markazi Provinces. The study ends with proposing some implications for educational stakeholders.